The sum we want is
![\displaystyle \sum_(n=0)^\infty ((-1)^(T_n))/((2n+1)^2) = 1 - \frac1{3^2} - \frac1{5^2} + \frac1{7^2} + \cdots](https://img.qammunity.org/2023/formulas/mathematics/college/6hrllbg9e4e3q9nn4za1n28dclt7sxn274.png)
where
is the n-th triangular number, with a repeating sign pattern (+, -, -, +). We can rewrite this sum as
![\displaystyle \sum_(k=0)^\infty \left(\frac1{(8k+1)^2} - \frac1{(8k+3)^2} - \frac1{(8k+7)^2} + \frac1{(8k+7)^2}\right)](https://img.qammunity.org/2023/formulas/mathematics/college/3q4juq1ctme0fr53ph1fhpef2hobrscofb.png)
For convenience, I'll use the abbreviations
![S_m = \displaystyle \sum_(k=0)^\infty \frac1{(8k+m)^2}](https://img.qammunity.org/2023/formulas/mathematics/college/7rwnd0xo5g0u2cvjrcaoezmph4yxru1dfg.png)
![{S_m}' = \displaystyle \sum_(k=0)^\infty ((-1)^k)/((8k+m)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/zkpgqkgxsolzfzd02fznlkk9o3xsfbt0zx.png)
for m ∈ {1, 2, 3, …, 7}, as well as the well-known series
![\displaystyle \sum_(k=1)^\infty ((-1)^k)/(k^2) = -(\pi^2)/(12)](https://img.qammunity.org/2023/formulas/mathematics/college/z7b9nbyj48b3ppazbj6ep2cv5bhmh4kw1s.png)
We want to find
.
Consider the periodic function
on the interval [0, 1], which has the Fourier expansion
![f(x) = \frac1{12} + \frac1{\pi^2} \sum_(n=1)^\infty (\cos(2\pi nx))/(n^2)](https://img.qammunity.org/2023/formulas/mathematics/college/3h69o9gdohh61j61e5qprcjoxvy46v6isu.png)
That is, since f(x) is even,
![f(x) = a_0 + \displaystyle \sum_(n=1)^\infty a_n \cos(2\pi nx)](https://img.qammunity.org/2023/formulas/mathematics/college/utm1i2c4pa2i2hirh7mv4doii2rflwwrbo.png)
where
![a_0 = \displaystyle \int_0^1 f(x) \, dx = \frac1{12}](https://img.qammunity.org/2023/formulas/mathematics/college/rnmrg0r396lkoglr08pv569xjtin44uwbd.png)
![a_n = \displaystyle 2 \int_0^1 f(x) \cos(2\pi nx) \, dx = \frac1{n^2\pi^2}](https://img.qammunity.org/2023/formulas/mathematics/college/1eamrd1x5y4hd3owyismxzhi9kjz57mh89.png)
(See attached for a plot of f(x) along with its Fourier expansion up to order n = 10.)
Expand the Fourier series to get sums resembling the
-s :
![\displaystyle f(x) = \frac1{12} + \frac1{\pi^2} \left(\sum_(k=0)^\infty (\cos(2\pi(8k+1) x))/((8k+1)^2) + \sum_(k=0)^\infty (\cos(2\pi(8k+2) x))/((8k+2)^2) + \cdots \right. \\ \,\,\,\, \left. + \sum_(k=0)^\infty (\cos(2\pi(8k+7) x))/((8k+7)^2) + \sum_(k=1)^\infty (\cos(2\pi(8k) x))/((8k)^2)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/81gcvml1ep5o6egxc9hb4v1i9w57jhyv2t.png)
which reduces to the identity
![\pi^2\left(\left(x-\frac12\right)^2-(21)/(256)\right) = \\\\ \cos(2\pi x) {S_1}' + \cos(4\pi x) {S_2}' + \cos(6\pi x) {S_3}' + \cos(8\pi x) {S_4}' \\\\ \,\,\,\, + \cos(10\pi x) {S_5}' + \cos(12\pi x) {S_6}' + \cos(14\pi x) {S_7}'](https://img.qammunity.org/2023/formulas/mathematics/college/hhjpadtg8xn066rl4zqfnq2y3gwdath8su.png)
Evaluating both sides at x for x ∈ {1/8, 3/8, 5/8, 7/8} and solving the system of equations yields the dependent solution
![\begin{cases}{S_4}' = (\pi^2)/(256) \\\\ {S_1}' - {S_3}' - {S_5}' + {S_7}' = (\pi^2)/(8\sqrt 2)\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/ymhu6w0uxfiyhh135inuj0dh0fxovtcfah.png)
It turns out that
![{S_1}' - {S_3}' - {S_5}' + {S_7}' = S_1 - S_3 - S_5 + S_7](https://img.qammunity.org/2023/formulas/mathematics/college/lzbub5z8syfrrlgfib2rfofvso8dqu8ajq.png)
so we're done, and the sum's value is
.